First record of bacterial canker (Clavibacter michiganensis ssp. michiganensis) on tomato in Cyprus - Psallidas, Petros G.; Glynos, P.; Ioannou, Nicolas (My University, 2000)
Symptoms of bacterial canker disease on tomato were first observed in June 1998, in three tomato fields in the semi-mountainous region of Eptagonia (Limassol district). In two of these fields, which were planted with cv. FA 179, infection was almost 100%, with heavy losses. The third field, planted with cv. Graziella, had only sporadic infections. An extensive survey during 1998-99 detected 10 additional cases of bacterial canker, all in the wider agro-ecological zone of initial disease detection. The pathogen Clavibacter michiganensis ssp. michiganensis was consistently isolated from diseased plants, identified, and its pathogenicity proved. This is the first report of bacterial canker disease on tomato in Cyprus.
Keywords: Lycopersicon esculentum; Birds-eye-spot; Seed-borne pathogen; Vascular wilt